Arabic Language Learning in Majelis Taklim: Approaches and Methods - Fasha, Julia; Siddiq, Mohammad; Azzahro, Fatimah (LADU: Journal of Languages and Education, 2025)
Background: Majelis taklim holds significant potential for Arabic language education through the application of varied and adaptive methods. The combination of traditional and modern methods can enhance teaching effectiveness if accompanied by appropriate strategies to overcome challenges. Thus, majelis taklim can continue to serve as a relevant and high-quality center for Arabic language learning for the Muslim community. Purpose: This article examines the methods and approaches to teaching Arabic in majelis taklim.. Design and methods: A qualitative paradigm using literature reviews was chosen to understand how aspects of Arabic language teaching methods can be formulated to meet the needs of majelis taklim. Results: In majelis taklim, various teaching approaches are employed, both traditional and modern. The combination of these approaches, along with the development of teaching methods and content, aims to support Islamic education, including Arabic language instruction. The preparation of teaching materials considers participants' backgrounds, particularly their age, and integrates traditional and modern methods. Commonly used Arabic teaching methods in majelis taklim include lectures and discussions, the grammar-translation method, as well as repetition and memorization techniques. The implementation of these methods must be adapted to address challenges such as limited time, diverse participant backgrounds, and restricted access to modern learning resources.